FACTORS THAT AFFECT PERFORMANCE ISLAMIC BANKS IN INDONESIA - Nidiatama, Fadel (UPT Publikasi Ilmiah UNISBA, 2024)
This study examines the effect of capital adequacy, investor customers, Sharia governance, debt-equity ratio and company size on financial performance at Islamic Commercial Banks in Indonesia for the period 2016-2021. The population in this research is all Islamic banks in Indonesia. The sampling technique used in this study is non-probability sampling, which uses the purposive sampling method. The sample of this study was 60 data from 10 selected Islamic banks. Data processing using Eviews 12.00. The data regression analysis method was used. The results showed that capital adequacy has a significant positive effect on financial performance, company size has a positive and significant effect on financial performance, sharia governance has a significant effect on financial performance, debt equity ratio has a negative and significant effect on financial performance and investor customers have no significant effect on the financial performance of Islamic banks in 2016 - 2021. Keywords : Financial Performance, Capital Adequacy, Sharia Governance, Debt-equity Ratio, Company Size.